Overweight and obesity in 16–18 years old teenagers in South Jakarta and the relationship with academic performance - Marie Christabelle; Bernie Endyarni Medise (World Nutrition Journal, 2020)
Objective: In different parts of the world, Indonesia included, overweight and obese people are seen to have worse performance compared to their healthy counterparts. Although there were research that had been done to observe the relationship between overweight, obesity, and academic performance, the results obtained were still divided into significantly and non-significantly related.Methods: A cross-sectional study was done to 373 students from two different schools in South Jakarta on December 2017–January 2018. Data was obtained by measuring height and weight of the participant to get his/her nutritional status and the average of participant’s odd semester Continual Assessment and Semestral Assessment of Academic Year 2017/2018 to see if the result was higher or equal to the passing grade.Results: Data analysis with chi square test shows that there was no significant relationship between overweight, obesity, and academic performance (p = 0.452 for Indonesian Language and p = 0.476 for Mathematics) although overweight and obese students tend to have better performance in some exam.Conclusion: The events that lead to overweight, obesity, and one’s academic performance are all multifactorial that the relationship between the two is difficult to be determined.